Shaking table test study of nuclear power plant model considering soil-structure interaction effect - Zhao, Jinyi; Chen, Hao; Zhou, Zhiguang (Soil dynamics and earthquake engineering (1984), 2023)
The influence analysis of site condition is fundamental to the seismic design of nuclear power plants. In this paper, a series of shaking table tests were performed to investigate the Soil-Structure Interaction (SSI) effect on the seismic response of nuclear power structures. An AP1000 nuclear power plant was taken as the objective structure, lead rubber bearings (LRBs) were used as the isolators and Shanghai silty clay was selected as the model soil. Test results show that (1) The soil has different effects on the dynamic characteristics of isolated and non-isolated model structures. (2) During the shaking table test, the foundation edge is subject to the highest soil pressure, and a contact surface separation between the foundation and the soil begins to occur under the seismic-margin earthquake (SME) seismic input level. (3) Both for the rigid and soil foundation, seismic isolation bearings can effectively reduce the acceleration response of the superstructure. (4) For the non-isolated model, the SSI effect significantly amplifies the seismic response at the bottom floor of the structure in the low frequency range, and an obvious rocking behavior occurs at the operating basis earthquake (OBE) seismic input level. (5) For the isolated model, the SSI effect reduces the hysteresis capacity of the seismic isolation system and amplifies the seismic response at the bottom floor, especially in the vertical direction. The site condition and the use of an isolation system have a significant impact on the seismic response of a nuclear power structure. Therefore, in the design and safety assessment of nuclear power plants, the influences of soil characteristics and isolation equipment in the soil-structure interaction system should be fully considered. •Model soil generally raised the damping ratio while decreasing the vertical fundamental frequency of the structural system.•Seismic response at the bottom floor of non-isolated model was greatly increased in the low frequency range by SSI effect.•Due to the SSI effect, the vertical PSA amplification for the isolated model was often greater in the low-frequency region.•The hysteresis capacity of seismic isolation systems was reduced when considering the SSI effect.